Self-Regulated Learning On Program Entry in Doctor of Physical Therapy Students: A Pilot Study. Issue 1 (13th March 2021) - Martin, Jennifer G.; Smith, Nancy S.; Wendt, Chris
Abstract : Introduction: The transition to graduate study can be difficult for entry-level physical therapist (Doctor of Physical Therapy [DPT]) students to make. One factor that may support this transition is the development of self-regulated learning (SRL). SRL has been associated with academic success in graduate health professions programs. Despite previous academic achievement, some DPT students struggle with first semester coursework. It is unknown whether these students have adequate SRL skills. Therefore, this study examined students' perceived SRL skills on program entry. Methods: Participants enrolled in their first semester of a DPT program were recruited from a medium-sized historically minority serving institution in the Southeastern United States. Doctor of Physical Therapy students ( N = 28) completed the Learning and Study Strategies Inventory (LASSI) instrument to discover perceived abilities in SRL. The LASSI is a valid and reliable instrument that assesses skills, strategies, and behaviors of SRL and has been used in other graduate health professions. Demographic data and LASSI scores were evaluated using descriptive statistics, and between-group comparisons were performed using nonparametric independent tests and analysis of variance. Significance was set at an alpha level of <.05. Results: Entering students perceived a need for moderate or high levels of support in most areas of SRL as measured by the LASSI. Statistically significant demographic differences in scale scores found within the cohort included minority status, undergraduate institution, and gender. Discussion/Conclusion: This study provides insights into the areas of support DPT students need for SRL that may have implications for early academic support. Diverse students may have different supportive needs. Further research is needed to discover SRL development needs in DPT students.